Reward Processing in the Brain: A Prerequisite for Movement Preparation? - M. Keitz; C. Martin-Soelch; K. L. Leenders (Neural Plasticity)
In the last decade, expanding animal studies on the cerebral organization of reward processing toward human in vivo situations has become possible. In this review, we define some of the concepts associated with reward, summarize the crucial importance of the dopaminergic system, and discuss the currently available neuroimaging studies in man. We will show that abstract concepts of human behavior like emotions, drive, arousal, and reinforcement are now open for further exploration in man at the level of neuronal circuit organization. The cerebral dopaminergic neurotransmitter circuitry does play an important role in the organization of both the motor and motivational system.